Patрoсonative Communication Stereotypes Of Internet Addiction In Members Of Anonymous Online Communities - Chugunov, V.; GorodokinА.; Shcherbina, V.; SkripnikА. (Psychiatry, Neurology and Medical Psychology, 2016)
In order to perform comparative analysis and to develop typology of pathological internet-specific patterns of communication in individuals with personologic-determined forms of internet-addiction and the participants of anonymous online communities, 80 respondents suffering from Internet-addiction according to the results of questionnaire Internet-UDIT were surveyed, among them 40 members of anonymous internet community, identifying themselves as Hikikomory (NEET), which declare social autoisolation. Such pathoconative communicative stereotypes were revealed: formally-communicative, compulsive, autistic, utilitary-communicative, alter natively-motivational, creatively-narcissistic and recreational, their specific characteristics and denotation were described.